Modeling a Thick Hydrogenated Amorphous Silicon Substrate for Ionizing Radiation Detectors - Davis, Jeremy Alexander; Boscardin, Maurizio; Crivellari, Michele; Fanò, Livio; Large, Matthew; Menichelli, Mauro; Morozzi, Arianna; Moscatelli, Francesco; Movileanu-Ionica, Maria; Passeri, Daniele; Petasecca, Marco; Piccini, Mauro; et al. (Frontiers in Physics, 2020)
There is currently a renewed interest in hydrogenated amorphous silicon (a-Si:H) for use in particle detection applications. Whilst this material has been comprehensively investigated from a numerical perspective within the context of photovoltaic and imaging applications, the majority of work related to its application in particle detection has been limited to experimental studies. In this study, a material model to mimic the electrical and charge collection behavior of a-Si:H is developed using the SYNOPSYS©Technology Computer Aided Design (TCAD) simulation tool Sentaurus. The key focus of the model is concerned with the quasi-continuous defect distribution of acceptor and donor defects near the valence and conduction bands (tails states) and a Gaussian distribution of acceptor and donor defects within the mid-gap with the main parameters being the defect energy level, capture cross-section, and trap density. Currently, Sentaurus TCAD offers Poole-Frenkel mobility and trap models, however, these were deemed to be incompatible with thick a-Si:H substrates. With the addition of a fitting function, the model was able to provide acceptable agreement (within 10 nA cm−2) between simulated and experimental leakage current density for a-Si:H substrates with thicknesses of 12 and 30 μm. Additional transient simulations performed to mimic the response of the 12 μm thick device demonstrated excellent agreement (1%) with experimental data found in the literature in terms of the operating voltage required to deplete thick a-Si:H devices. The a-Si:H model developed in this work provides a method of optimizing a-Si:H based devices for particle detection applications.